2015
DOI: 10.3934/mbe.2015.12.1203
|View full text |Cite
|
Sign up to set email alerts
|

The role of the cytokines IL-27 and IL-35 in cancer

Abstract: The cancer-immune interaction is a fast growing field of research in biology, where the goal is to harness the immune system to fight cancer more effectively. In the present paper we review recent work of the interaction between T cells and cancer. CD8+ T cells are activated by IL-27 cytokine and they kill tumor cells. Regulatory T cells produce IL-35 which promotes cancer cells by enhancing angiogenesis, and inhibit CD8+ T cells via TGF-β production. Hence injections of IL-27 and anti-IL-35 are both potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…There is no study regarding the relationship between IL‐35 and H. pylori infection. However, elevated levels of IL‐35 were reported in patients with hepatitis B virus infection, especially in those with higher viral load, in patients with active tuberculosis, in patients with leprosy, and in patients with malignant diseases . Furthermore, circulating levels of IL‐35 are aberrant in patients with multiple sclerosis (MS), allergic asthma, inflammatory bowel disease, autoimmune thrombocytopenia, periodontitis, and coronary artery diseases …”
Section: Discussionmentioning
confidence: 99%
“…There is no study regarding the relationship between IL‐35 and H. pylori infection. However, elevated levels of IL‐35 were reported in patients with hepatitis B virus infection, especially in those with higher viral load, in patients with active tuberculosis, in patients with leprosy, and in patients with malignant diseases . Furthermore, circulating levels of IL‐35 are aberrant in patients with multiple sclerosis (MS), allergic asthma, inflammatory bowel disease, autoimmune thrombocytopenia, periodontitis, and coronary artery diseases …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the immunerelated cytokines are considered as crucial molecules during tumor development. IL-27 and IL-35 are 2 important members of the cytokine family and have been investigated in diverse cancers [21]. As a gene coding for a component of both IL-27 and IL-35, elevated EBI3 expression has been detected in lung cancer and was described as a potential biomarker for use in targeted therapy [18].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been found that IL-27 produces strong antitumor effects against different tumour models through a variety of mechanisms in various cancer cell lines and in vitro, not only by exerting direct effects on the tumor cells but also by activating anti-tumor immune responses [20], including IL-27 antitumor, anti-inflammatory and antiangiogenic effects-mediated activities and activation of natural killer (NK) cells antimetastatic activities [21].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, due to the non-toxicity of IL-27 in previous clinical studies and the discovery of its anticancer properties in other examined tumours [20], the present study investigated the use of IL-27 as an approach to the diagnosis of lung cancer. This study is also the first one to examine the association between IL-27 concentration and lung cancer according to the type of tumour.…”
Section: Introductionmentioning
confidence: 99%